Human Security and Epidemics in Africa: Learning from COVID-19, Ebola and HIV - Velthuizen, Andreas; Varin, Caroline (Routledge Studies in Peace, Conflict and Security in Africa, 2024)
This book examines the impact of epidemics in Africa, exploring some of the adaptation and crisis management strategies adopted to tackle COVID-19, Ebola, and HIV-AIDS. The authors reflect on lessons learned from solving complex problems and difficult decisions made by leaders on pandemic management to shape the security environment and, thus, the well-being of people living in Africa for years to come. Drawing on cases from across the continent, the book demonstrates that, significantly, during the COVID-19 pandemic, African countries and communities frequently displayed regional solidarity, creativity in decision-making, decisiveness in dealing with corruption and opportunism, and resilience and discipline in implementation. Adopting a human security framework, the authors share their lived experiences and explore the impact of epidemics on public policy decision-making, foreign policy implementation, global relations, collaboration in the community dimension, and, ultimately, the future of socio-economic development in Africa. This book will be a welcome addition for practitioners and researchers across the fields of security studies, health management, and African studies, making an essential contribution to the security discourse in a post-COVID world.